Are Value At Risk And Maximum Drawdown Different From Volatility In Stock Market? - Kim, Soo-Hyun (Journal of Applied Business Research, 2018)
Measuring risk is the key component in many asset pricing models. Although volatility is the most widely used measure for the risk, Value at Risk (VaR) and Maximum drawdown (MDD) are also considered as alternative risk measure. This article questions whether VaR and MDD contain additional information to volatility in equity market. The empirical analysis is conducted using the stocks listed in Korean stock market. By constructing portfolios in accordance with three risk measures, cross-sectional predictability is tested. The primary findings are as follow; (1) the return patterns are bell shaped in all measures and (2) VaR and MDD do not capture additional risk factors after conditioning volatility.
Keywords: Value at Risk; Maximum Drawdown; Risk Management